Associations between anthropometric characteristics and physical performance in male law enforcement officers: a retrospective cohort study. Issue 1 (December 2016) - Dawes, James; Orr, Robin; Siekaniec, Claire; Vanderwoude, Andrea; Pope, Rodney
Abstract Background Police officers are often required to undertake physically demanding tasks, like lifting, dragging and pursuing a suspect. Therefore, physical performance is a key requirement. Methods Retrospective data for 76 male police officers (mean age = 39.42 ± 8.41 years; mean weight = 84.21 ± 12.91 kg) was obtained. Data included anthropometric (skinfolds, estimated percentage body fat, lean body mass and fat mass) and physical performance (1 Repetition Maximum Bench Press, 1–min sit-ups, 1-min push-ups, vertical jump, 300 m run, 1.5 mile run) measures and correlations between anthropometric measurement and fitness score were obtained. Results Estimated percentage body fat was significantly (p ≤ .001) and negatively correlated with all performance measures, except sit-ups and 300 m and 1.5 mile run performance. Estimated lean body mass was significantly and positively (p ≤ .001) correlated with push-ups, bench press and vertical jump measures, while increasing estimated fat mass was significantly (p ≤ .001) associated with reduced performance on sit-up, vertical jump, 1.5 mile run and estimated maximal voluntary oxygen uptake. Conclusions A targeted approach, going beyond just decreasing percentage body fat to also selectively increasing lean mass, should be applied for optimal improvement in physical fitness performance.